Potatoes, Including French Fries, Contribute Key Nutrients to Diets of U.S. Adults: NHANES 2003-2006 - Freedman, Marjorie R.; Keast, Debra R. (Journal of Nutritional Therapeutics, 2012)
ABSTRACT Many adult Americans fail to meet nutrient requirements. The objective of this study was to examine 24-hour dietary recall data from NHANES 2003-2006 to test the hypothesis that white potatoes (not sweet potatoes) contributed important nutrients within energy needs to adults’ diets. Potato content of survey foods was determined using US Department of Agriculture (USDA) recipe databases (Standard Reference [SR]-Link files). SR codes were linked to USDA food composition data to determine nutrient content. Daily nutrient intakes among consumers of potatoes (including french fries [FF]), and consumers of FF alone, were determined by applying the composition database to respondent’s recall data. Sample weighted data were analyzed; t-tests assessed differences between age-sex groups. Approximately 35% of adults consumed potatoes; 12% consumed FF. Intakes were lowest in adults aged 51+ y (P < .01). More males, compared to females, consumed potatoes (P<.05) and FF (P< 0.01). Males consumed larger amounts of potatoes (127 g/d) and FF (85 g/d) (P< .01). In all age-sex groups, potatoes and FF provided 7-11% of total energy (within daily energy requirements); 3-14% of daily fat (>75% MUFA+PUFA); >15% dietary fiber, >13% vitamin B6 and potassium; >5% thiamin, niacin, phosphorus, magnesium and copper; and <5% sodium. Potatoes provided >10% vitamin C for all age-sex groups and >5% vitamin K and iron for most groups; FF provided >5% vitamin E and folate intakes for all. These cross-sectional data showed that potatoes and FF, in amounts consumed by adults, contributed important nutrients in line with dietary recommendations.